CFRP manufacturing method by using electro-activated deposition and the effect of reinforcement with carbon fiber circumferentially around the hole. (1st January 2019) - Katagiri, Kazuaki; Honda, Shinya; Minami, Sayaka; Tomizawa, Yusuke; Kimu, Daiki; Yamaguchi, Shimpei; Ehiro, Takuya; Ozaki, Tomoatsu; Sonomura, Hirosuke; Kawakita, Sonomi; Takemura, Mamoru; Yoshioka, Yayoi; et al.
Abstract: For the efficient manufacturing of carbon fiber reinforced plastics (CFRP), the electro-activated deposition resin molding (ERM) method is developed. The carbon fiber fabric is immersed in an electro-activated deposition solution containing polymer with epoxy groups. By energization, an epoxy resin is precipitated on the surface of the carbon fiber, and impregnation occurred in the solution. In this study, applying the ERM method, CFRP specimen with the hole was manufactured. Furthermore, the reinforcement by arranging the fiber circumferentially around the hole was installed. The carbon fiber fabric was sewn using the tailored fiber placement (TFP) machine. As a results, the effect of the reinforcement was confirmed. The tensile strength of CFRP with the hole and the reinforcement was the same as in the case without the hole. From the finite element analysis, it was confirmed that the reinforcement around the hole reduced the stress concentration.